Analysis of Antioxidant Activity of Curcumin Extract from White Turmeric (Curcuma zedoria) and Yellow Turmeric (Curcuma longa) Using Soxhletation Method - Vivi Shofia; Anggraeni, Adek Bela; Nurlaila, Hamida (Indonesian Journal of Science and Pharmacy, 2024)
Turmeric has been a staple in traditional medicine and cuisine in various countries. Tumeric contains the main bioactive compound, namely curcumin. Curcumin is recognized as antioxidants that can which donate one or more electrons to free radicals, effectively neutralizing them. The commonly used turmeric varieties are white turmeric (Curcuma zedoaria) and yellow turmeric (Curcuma longa). White turmeric is characterized by its white rhizome, while yellow turmeric has a yellow rhizome. Both varieties contain curcumin, but their antioxidant activities must be fully elucidated. The Soxhlet method is a common technique employed for curcumin extraction. This study investigated the antioxidant activity of white turmeric and yellow turmeric compared to vitamin C. The DPPH method was used to assess antioxidant activity. The findings revealed that white turmeric (Curcuma zedoaria) and yellow turmeric (Curcuma longa) extracts exhibited antioxidant activity with IC50 values of 12.39 µg/mL and 44.065 µg/mL, respectively. Conversely, vitamin C showed an IC50 value of 19.95 µg/mL. These results indicate that yellow turmeric curcumin extract possesses superior antioxidant activity compared to white turmeric and vitamin C, falling within the category of solid antioxidants with IC50 values below 50 µg/mL.